Etika dan Hukum dalam Penggunaan Data Pribadi: Menjembatani Kesenjangan antara Kepatuhan Formal dan Tanggung Jawab Moral di Era Data-Driven Society - Gilang Rizki Aji Putra (BULETIN ADALAH, 2022)
This article analyzes the ethical and legal dimensions of personal data use in the digital economy, focusing on Indonesia’s PDP Law (Law No. 27/2022). It assesses the gap between legal compliance and ethical responsibility in data governance. Using normative legal research with conceptual and philosophical approaches, the study finds misalignment between legal standards and ethical expectations. Key principles such as fairness, algorithmic transparency, and user autonomy are not fully reflected in regulation. Digital lending cases show formal compliance may conflict with ethical expectations requiring stronger ethical integration in governance systems. Keywords: Ethical Data, Data Protection Law, Formal Compliance, Fairness, Algorithmic Transparency